ФОРМУВАННЯ КУЛЬТУРИ ПЕДАГОГІЧНОГО СПІЛКУВАННЯ ЗАСОБАМИ ДІАЛОГІЧНИХ НАВЧАЛЬНИХ СИТУАЦІЙ (Педагогіка вищої та середньої школи, 2022)
The article considers the problem of formation of the Culture of pedagogic Intercourse, reveals the recessity of making up. the dialogue training situations, and shows the positive dynamics of the levels of the culture of pedagogic intercourse.